The impact of video versus text reviews on consumer intention to purchase - Albano, P.; Guerreiro, J. (2019 14th Iberian Conference on Information Systems and Technologies (CISTI), 2019)
The current study evaluates the contribution of online video reviews in comparison with the traditional text reviews in purchase decisions. Therefore, we analyze issues such as types of consumers, types of reviews, purchase intention and how the combination of different scenarios may explain if in fact video reviews have a differential impact on the purchase decision compared to text reviews. A quantitative method for the development of the research was adopted through a survey. The sample achieved a total of 153 responses. Results show that video reviews have more impact on consumers' buying decisions than text reviews, both in terms of consumer type, product type and the credibility of the review assumes a preponderant role in the development of consumer perception of product quality, thus having a greater impact on their purchasing decision